A Capability Approach to Justice as a Virtue - Drydyk, Jay (Ethical theory and moral practice, 2012)
In The Idea of Justice, Amartya Sen argues for an approach to justice that is comparative and realization-based rather than transcendental and institutional. While Sen’s arguments for such an approach may not be as convincing as he thought, there are additional arguments for it, and one is that it provides a unique and valuable platform on which an account of justice as a virtue of social and political actors (including institutions and social movements) can be built. Hence new dimensions of comparison are opened up: some actors are better disposed and more successful than others at leading social change in the direction of greater justice. The main objective of this article is to use the capability approach to construct such an account. Six dimensions of acting justly are identified: (1) reducing capability shortfalls; (2) expanding capabilities for all; (3) saving the worst-off as a first step towards their full participation in economy and society, (4) which is also to be promoted by a system of entitlements protecting all from social exclusion; while (5) supporting the empowerment of those whose capabilities are to expand; and (6) respecting ethical values and legitimate procedures. I conclude by sketching some underlying moral psychology.